Analysis of the Impact of Soil Quality on System Effectiveness Grounding Lightning Rod On Project JoMA Boutique Villas and Resort - Putra, I Komang Aditia Triguna; Pancane, I Wayan Dikse (Journal of Development Research, 2025)
The grounding system is a crucial element in lightning protection because it channels current to the ground for the safety of buildings, equipment, and humans. This study evaluated the grounding resistance at the JoMA Boutique Villa & Resort project and assessed its effectiveness based on the SNI 03-7015-2004, IEEE Std 80-2013, and NFPA 780 standards, which stipulate a maximum limit of 5 Ω. Measurements at four electrode points using an earth tester yielded values of 2.41 Ω, 0.23 Ω, 0.11 Ω, and 0.22 Ω. All results were well below the standard, with effectiveness ranging from 207.47% to 4545.45%. Variations in values were influenced by soil conditions, where embankment soil had higher resistance than wet clay soil. Overall, the grounding system at the study site proved to be highly effective and reliable in protecting buildings and electronic equipment, as well as reducing the risk of step and touch voltages that endanger human safety.